Plant Disease Diagnostic Capabilities in Venezuela: Implications for Food Security - Marys, Edgloris; Rosales, Ligia Carolina (Frontiers in Sustainable Food Systems, 2021)
Venezuela is currently experiencing the most severe humanitarian crisis in the Americas of this century. Little food is being produced locally, despite the population's right to food. Plant disease outbreaks are causing substantial declines in major staple food and cash crops, and this impacts on rural livelihoods, and poses a significant and growing threat to the already complex food insecurity crisis in the country. Nonetheless, phytosanitary services and hence the control of plant pests and diseases have been substantially weakened over the recent years as a consequence of the collapse of the economy and the substantial deterioration of government services. Therefore, most of the pathogens associated with symptoms-causing diseases remain unidentified or uncharacterized, and no surveillance or crop protection strategies have been implemented. In this review, we address the country's issues and challenges in diagnosing, monitoring and managing plant diseases to restore national food security.